Enzymatic activity and bacterial community profile in soil under solarization e biofumigation - Passos, Samuel Ribeiro; Junior, Fábio Bueno dos Reis; Rumjanek, Norma Gouvêa; Mendes, Ieda de Carvalho; Baptista, Miriam Josefina; Xavier, Gustavo Ribeiro (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effects of solarization and biofumigation on the soil microbial communities, by means of beta-glucosidase activity and 16S rDNA PCR-DGGE analyses. Solarization with a plastic covering of the soil took place over two, four and six months, and the soils were biofumigated by the addition of 2 and 5% (v/v) of chicken litter to the soil. Right after the plastic cover removal and after 30 days, beta-glucosidase was lower than in the nonsolarizated control. After 60 days, there were no longer significant differences in beta-glucosidase activity between treatments. The addition of 5% chicken litter stimulated beta-glucosidase activity. Bacterial community profile was influenced by solarization time, regardless of time of plastic cover removal. There was no effect of chicken litter amendments over the bacterial community structure. Solarization affects beta-glucosidase activity but, after 60 days, its effects are no longer detectable, differently of the observed data regarding soil bacterial community structure by PCR-DGGE. Biofumigation stimulates beta-glicosidase activity, but it doesn't affect the bacterial community structure.
Keywords: beta-glucosidase; chicken litter; microbial diversity; microbial ecology; soil management; 16S rDNA